Predicting offensive performance in collegiate baseball players using isometric force production characteristics - Bailey, C. A.; Sato, K.; Hornsby, W. G.; Yamada, K.; Fujinaga, T.; Nishita, K.; Seki, M.; Yamamoto, H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to examine kinematic differences between `one-footed` and `two-footed` players when kicking with the non-preferred leg at a target and with maximal effort. Eighteen highly-trained young soccer players were categorised as one-footed (n=9) and two-footed (n=9) based on results of a kicking test. Motion analysis data showed that two-footed players run-up straighter and have less pelvic rotation at ball-foot impact than one-footed players and the differences are likely to be meaningful (ES differences of 0.89 and 0.99 respectively). Run-up angle and pelvic rotation angle are significantly correlated (P < 0.1). The study found that two-footed players are significantly smaller in stature than one-footed players (P < 0.1). Practical implications for soccer coaches arose from the study